Practices and challenge of the Scientific Society of Dental Students as a seedbed for university research - Yuri Alejandro Castro Rodríguez (Editorial Ciencias Médicas, 2022)
Introduction: The Scientific Student Societies are extracurricular learning communities that are based on research hotbeds as a strategy of formative research to promote the development of investigative competencies. Objective: To describe the practices and challenges of a Scientific Society of Dental Students. Methods: An ethnographic study was designed that followed the activities of the Society of Dental Students of the Universidad Nacional Mayor de San Marcos (Lima, Peru) for a period of nine months in 2019. The techniques of participant observation and documentation were used. The categories studied were seedbed identity, practices carried out in the seedbed and challenges. Results: The Society of Dental Students was created in 2014; it is identified as a learning community where the student is provided with methodological and conceptual tools to develop their research skills. A president, advisers, and permanent committees lead it. His main practices are academic, scientific and of social projection. The students report that it has allowed them to experience how a research project was made, from its conception to its publication. Conclusions: It is concluded that the Scientific Society of Dental Students is a research hotbed with six years of experience and is identified as a place where the student learns elements and processes of research from the same investigative act; its main one is the formalization of the seedbed, since its foundation, the faculty and authorities have not recognized the seedbed as an institution.